NOTÒLIQ OILANING IJTIMOIY-PEDAGOGIK MUAMMOLARI - Raxmatova Xurriyat (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This paper analyzes the main social and pedagogical problems arising in the process of development of children growing up in single-parent families. The study highlights the impact of the absence of a father or mother on the child's formation as a person, their psychological state, and social adaptation. Furthermore, practical recommendations are provided regarding the methods of socio-pedagogical assistance that  should  be  offered  to  children  from  single-parent  families  by  educational institutions and local communities.